Chemical, chromatic, and sensory attributes of 6 red wines produced with prefermentative cold soak - Casassa, Luis Federico (2015)
Six red grape cultivars, Barbera D’Asti, Cabernet Sauvignon, Malbec, Merlot, Pinot Noir and Syrah, were produced with or without prefermentative cold soak (CS). Cold soak had no effect on the basic chemical composition of the wines. At pressing, CS wines were more saturated and with a higher red component than control wines. After 1 year of bottle aging, CS wines retained 22% more anthocyanins than control wines, but tannins and total phenolics remained unaffected. Both saturation and the red component of colour were slightly higher in CS wines. From a sensory standpoint, CS only enhanced colour intensity in Barbera D’Asti and Cabernet Sauvignon wines, whereas it diminished colour intensity in Pinot Noir. Cold soak had no effect on perceived aroma, bitterness, astringency, and body of the wines. Principal Component Analysis suggested that the outcome of CS is contingent upon the specific cultivar to which the CS technique is applied.